Fossil rodents in Mylodon Cave as indicators of late Pleistocene-Holocene environmental evolution in southern Chile - Pardinas, Ulyses F. J.; Borrero, Luis; Martin, Fabiana Maria; Massone, Mauricio; Fernandez, Fernando J. (My University, 2022)
We conducted the first taphonomic and paleoenvironmental study based on late Pleistocene-Holocene small mammal remains recovered from the famous Mylodon Cave (Cerro Benitez area, ultima Esperanza, Chile). Most of the analyzed material came from the extensive excavations made by Earl Saxon in 1976. We also studied late Holocene small mammal samples of the neighboring rock shelter Dos Herraduras 1. Analyzed remains were mostly produced by owls, probably living inside the caves. In Mylodon Cave, the higher values of girdle bones are consistent with a windblown litter. We recorded nine species of rodents, seven cricetids, and two caviomorphs; almost all the identified taxa integrate recent local communities. Late Pleistocene-Holocene assemblages are characterized by the chinchilla rat Euneomys, indicating unforested areas around the caves under cold and moist climatic conditions. Middle Holocene amelioration is reflected by incremental rodent species richness, including the first record of taxa clearly associated with forest (e.g., Abrothrix lanosa). Late Holocene assemblages are markedly stable, indicating local conditions similar to the current (historical) environment. Quaternary rodents from Cerro Benitez area do not indicate abrupt environmental changes during middle-late Holocene, but a progressive trend towards forest increase.
Keywords: cerro benitez; cricetidae; ctenomys; dos herraduras 1; euneomys; nothofagus forest; patagonian steppe; saxon; ultima esperanza